2017
DOI: 10.1021/acs.orglett.7b00057
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodifferentiation in the Photoisomerization of (Z,Z)-1,3-Cyclooctadiene in the Cavity of γ-Cyclodextrin–Curcubit[6]uril-Wheeled [4]Rotaxanes with an Encapsulated Photosensitizer

Abstract: A biphenyl photosensitizer axle was implanted into the cavities of native and capped γ-cyclodextrins through rotaxanation using a cucubit[6]uril-templated azide-alkyne 1,3-dipolar cycloaddition, resulting in the construction of highly defined chiral binding/sensitizing sites. The orientation and interaction of the axle and capping moieties at the ground and excited states were interrogated by NMR, UV-vis, circular dichroism, and fluorescence spectroscopic studies. In situ photoisomerization of (Z,Z)-1,3-cycloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
(16 reference statements)
3
50
0
3
Order By: Relevance
“…The plots of ln(θ 0 /θ t ) against time gave straight lines, supporting the first-order kinetic model [25]. Increasing the temperature usually increases the reaction kinetics, and we have demonstrated that the temperature is critical for affecting the molecular recognition and stereoselectivity of supramolecular photochirogenesis [26][27][28][29][30][31][32][33]. To understand the temperature effect on the racemization of BP-f1, the CD ex versus time was recorded at different temperatures.…”
Section: Bp-f1supporting
confidence: 66%
“…The plots of ln(θ 0 /θ t ) against time gave straight lines, supporting the first-order kinetic model [25]. Increasing the temperature usually increases the reaction kinetics, and we have demonstrated that the temperature is critical for affecting the molecular recognition and stereoselectivity of supramolecular photochirogenesis [26][27][28][29][30][31][32][33]. To understand the temperature effect on the racemization of BP-f1, the CD ex versus time was recorded at different temperatures.…”
Section: Bp-f1supporting
confidence: 66%
“…[9] We have demonstrated that CDsa re particularly suitable for conducting supramolecular photochemical reactions because these molecules are UV transparent. [10] g-CD-based A1 and A2 showedl argely improved solubility (> 5.0 mM)r elative to A3 (< 0.2 mM)i n aqueous solution of pH 9.0 by virtue of the excellent water sol- Figure 1. Schematic illustration of the TTA-UC process.…”
Section: Resultsmentioning
confidence: 99%
“…The CD and UV spectra were measured in a CH 2 Cl 2 solution of enantioenriched 8 derivatives (Figure 13c), which shows the CD signals of the mirror image, indicating that the compounds are of opposite bowl chirality. Recently, Yang and co-workers prepared azonia [6]helicene tethered with supramolecular host β-cyclodextrin, and used a chirality sensing probe for underivatized amino acids in water [89][90][91][92][93][94]. Indeed, tethered azonia [6]helicene acts as a conformationally robust chiral auxiliary to improve the chiral recognition ability of native cyclodextrins.…”
Section: Racemic (±)-21 Was Prepared By Aerobic Oxidation Of Racemic mentioning
confidence: 99%